Developing An Inclusive Service Model for Persons with Disabilities in University Sexual Violence Prevention and Response Task Forces: Findings from A Focus Group Discussion at Universitas Sumatera Utara - Meutia Nauly; Hairani Siregar; Suri Mutia Siregar; Narosu Siregar; Patricia Srisere Ikaria Situmorang (Randwick International of Social Science Journal, 2026)
Sexual violence prevention and response in higher education require institutional systems that ensure equitable access for all members of the academic community, including persons with disabilities. Despite the establishment of Sexual Violence Prevention and Response Task Forces (Satgas PPK) in Indonesian universities, evidence on disability-inclusive service models remains limited. This study aimed to identify barriers to accessible support services and develop an inclusive service model for university-based task forces using a participatory approach. A qualitative study was conducted through a Focus Group Discussion (FGD) involving multidisciplinary stakeholders, including task force members, academics, disability advocates, legal aid organizations, government agencies, and an international partner from Universiti Sains Malaysia. Data were analyzed using thematic analysis. Five major themes emerged: (1) barriers to accessible reporting and service utilization, (2) strengthening faculty-based peer support, (3) victim-centered and disability-inclusive services, (4) multidisciplinary referral pathways, and (5) institutional governance for sustainable services. The findings highlight the importance of integrating accessible reporting, trained peer supporters, coordinated psychosocial and legal assistance, and institutional policies supported by permanent organizational structures. The proposed Inclusive Service Model emphasizes accessibility, collaboration, and institutional commitment as key elements of sustainable violence prevention and response in higher education, providing practical and policy recommendations for strengthening inclusive governance and protecting persons with disabilities.